2020
DOI: 10.1016/j.oraloncology.2020.104860
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy is a preferred option for oral cancer patients during COVID-19 pandemic?

Abstract: Table 1 Status and strategies for oral cancer patients during COVID-2019 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Full-text articles were retrieved and reviewed in detail. From 188 references, 154 were reviews, 6 studies did not provide any definition for Treg markers, [39][40][41][42][43][44] one paper did not use appropriate Treg markers, 45 1 study did not present the results of Treg evaluation, 46 4 articles were commentary, [47][48][49][50] and 2 papers were hypothesis. 51,52 Twenty studies were included in the methodological quality assessment.…”
Section: Literature Search and Quality Of Included Studiesmentioning
confidence: 99%
“…Full-text articles were retrieved and reviewed in detail. From 188 references, 154 were reviews, 6 studies did not provide any definition for Treg markers, [39][40][41][42][43][44] one paper did not use appropriate Treg markers, 45 1 study did not present the results of Treg evaluation, 46 4 articles were commentary, [47][48][49][50] and 2 papers were hypothesis. 51,52 Twenty studies were included in the methodological quality assessment.…”
Section: Literature Search and Quality Of Included Studiesmentioning
confidence: 99%
“…They concluded that primary radiotherapy and chemoradiotherapy were inferior to surgical management for oral squamous cell carcinoma. Nevertheless, in this special COVID-19 pandemic situation, if there is a lack of medical resources to protect patients from COVID-19 infection, it has been suggested that surgery could be replaced with concurrent chemoradiation therapy, radiation therapy or immunotherapy temporarily to slow disease progression 8 .…”
mentioning
confidence: 99%